2022
DOI: 10.3390/ijerph19074214
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Different Large-Sided Games and Official Matches on Professional Football Players’ Locomotor Intensity

Abstract: Large-sided games (LSG) are commonly used in the training contexts for providing either technical/tactical or locomotor/physiological stimuli. Despite natural similarities with the official match, the locomotor profile seems to be different, which must be considered by the coaches to identify compensatory strategies for achieving the ideal dose of training. The aim of this study was two-fold: (1) to investigate the locomotor demands imposed by LSGs and the official matches; and (2) to compare the effect of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the other hand, 10 vs. 10 + 1F + 2GK was the only format with mean values similar to matches for most variables of the study (except in MS). Other studies have found that larger pitch sizes caused an increase in TD and mechanical work, but with more relative playing area per player designs (10 vs. 10 + 2GK; 291 m 2 per player; Caldeira et al, 2022). In another comparison among different large-sided game formats (8 vs. 8 and 10 vs. 10, among others) with matches, only 10 vs. 10 (342 m 2 per player) allowed players to reach similar running intensities to those of competition (TD and high-intensity running at speed > 14.4 km/h) (Lacome et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, 10 vs. 10 + 1F + 2GK was the only format with mean values similar to matches for most variables of the study (except in MS). Other studies have found that larger pitch sizes caused an increase in TD and mechanical work, but with more relative playing area per player designs (10 vs. 10 + 2GK; 291 m 2 per player; Caldeira et al, 2022). In another comparison among different large-sided game formats (8 vs. 8 and 10 vs. 10, among others) with matches, only 10 vs. 10 (342 m 2 per player) allowed players to reach similar running intensities to those of competition (TD and high-intensity running at speed > 14.4 km/h) (Lacome et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…It could provide a more accurate measure of the physical demands of a match or training session than simply measuring the total distance covered ( Pillitteri et al, 2023a ). ED considers that different movements have varying metabolic demands and thus contribute differently to a player’s overall physical workload ( Osgnach et al, 2010 ; Caldeira et al, 2022 ). It was demonstrated that the equivalent distance index (EDI), the ratio between the ED and the total distance covered in a match or TGs, showed a strong correlation with accelerations and decelerations events; for this reason, both metabolic and traditional approaches based on time spent in arbitrarily chosen running speed categories should be used together for load monitoring in professional soccer players.…”
Section: Introductionmentioning
confidence: 99%